PENGARUH BYSTANDER EFFECT DAN WHISTLEBLOWING TERHADAP KECURANGAN LAPORAN BANTUAN KEUANGAN PARTAI POLITIK (STUDI EKSPERIMEN PADA MAHASISWA PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNDANA) - Yohana Febriani Angi, Maria Indriyani Hewe Tiwu (LPPM University 17 Agustus 1945 Samarinda, 2022)
AbstractThis study aims to (1) Determine the effect of the observer's impact on reducing party financial assistance funds; (2) Knowing the effect of whistleblowing on opposing fraud and (3) studying the effect of observers and complaints on the increase in party political aid funds. Testing the hypothesis in this study using an experimental instrument. The factors consist of two variables, namely the adequacy of financial statements as the dependent variable, the observer effect and the complaint as an independent variable. The population in this study were all students of FEB Accounting Study Program, Nusa Cendana University. The sampling technique using purposive sampling method. The criteria used as research correspondents are students who have received and taken Business Law and Ethics courses. The data used in this study are primary data obtained directly from the research object in several research results. The Rating Scale used in this study uses a Likert Scale. The results show that the bystander effect affects the reduction of financial aid for political parties. Whistleblowing plays a role in reducing the fraud on financial statements of political parties. And the effect observer and whistleblowing influence simultaneously towards reducing the adequacy of political party financial assistance. Keywords: Bystander effect, whistleblowing, Fraudulent Reports on political party financial assistance